The perceptions of gynecologic oncology fellows on readiness for subspecialty training following OB/GYNRESIDENCY - Renata R. Urban; Amin A. Ramzan; David W. Doo; Jeanelle Sheeder; Saketh R. Guntupalli (Elsevier, 2019)
A recent survey of fellowship program directors (PD) within gynecologic oncology (GO) noted concerns regarding the abilities of incoming fellows. The objective of this study was to evaluate the perceptions of current and former fellows in gynecologic oncology of their readiness for fellowship training. A previously used survey was modified and distributed in 2016 to current and former fellows in GO. The survey explored domains of independent practice, psychomotor ability, clinical evaluation and scholarship. A standard Likert scale was employed and domains/responses were tailored to the subspecialty. A total of 150 current and recently former fellows responded to the survey, for a response rate of 38.7%. Nearly 70% of respondents reported being able to independently perform a hysterectomy when starting fellowship, and nearly 50% felt they could perform lysis of adhesions either without assistance. Although nearly 95% reported having had the opportunity to develop a plan of action for patients on labor and delivery, only 40.7% felt able to independently manage postoperative complications without assistance. Common themes that emerged in the open-ended responses pertained to self-perception of inadequate surgical skills and knowledge specific to gynecologic oncology. Although the majority of current and former fellows in gynecologic oncology report feeling prepared for fellowship, themes noted in the open-ended responses suggest a lack of confidence in surgical skills and clinical knowledge. Keywords: Graduate medical education, Fellowship, Gynecologic oncology, Bootcamp